PENERAPAN E-FORM PADA PENINGKATAN KEPATUHAN WAJIB PAJAK DALAM PENYAMPAIAN SPT TAHUNAN - Nicholas Danendra Pratama; Dwi Suhartini (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
DJP as the tax regulator in Indonesia always strives to increase state revenue as the foundation for the running of the country by improving tax compliance. Taxpayer compliance supporting the increase in annual tax revenue, so the DJP provided a breakthrough in the form of digitizing tax reporting by moving the service and reporting system online, then in 2017 a system was created to improve tax services and reporting in the form of e-form as a tax return reporting facility which is expected to facilitate reporting and increase the level of tax compliance. The purpose of this study is to determine whether the digitalization factor in the form of e-form can have an impact on taxpayer compliance. The research method uses a descriptive qualitative approach. The data used in the study were taken from literature studies totaling 6 reference journal articles. The study results can be concluded that e-form has a better significant effect on increasing tax compliance.